Demographic and health issues in the polish population versus types of tasks regarding health education - Piecewicz-Szczęsna, Halina; Karwat, Irena Dorota (Polish Journal of Public Health, 2010)
The knowledge of demographic and health issues of the Polish population comprises the fundamentals of any preventive as well as diagnostic-therapeutic and educational action. The trends in some health, demographic and social phenomena have been changing recently. These problems are strictly connected with various types of educational needs as well as tasks concerning their realisation. The objective of this work was to determine some educational tasks for medical personnel as a result of the epidemiological analysis of the trends concerning health and demographic problems observed in the Polish population. The epidemiological analysis showed that the following health problems in the Polish population are responsible for high ratios in the mortality structure: cardiovascular diseases (45.4%), malignant diseases (24.6%) and injuries as well as food poisoning (6.6%). These problems are strictly related to the need of constant education of the population in the field of cancer prevention, the prophylaxis of cardiovascular diseases, and prevention of traumas, injuries, and food poisoning. There is also a growing need for further education among women in different stages of their lives since the parity index has decreased while the population growth rate is low (and even negative in some regions). The ageing population as well as an increasing number of the disabled also belong to the group of significant health-demographic problems. As a result, not only further education regarding self-care is needed for the elderly and the disabled, but also the rest of the society should be taught how to take non-professional care of those who need it. Furthermore, some problems belonging to the group of social pathology has noted a constant increase tendency, e.g. drug addiction and alcoholism, demanding bigger financial resources on health education towards the prophylaxis of theses addictions. The above-mentioned types of problems indicate that health education should put the emphasis on disease prevention, teaching the disabled and the elderly how to perform their self-care activities as well as show their carers what non-professional care should be like. Further epidemiological analysis is necessary in order to determine educational needs of each population age group, directions and methods how the shortages in educational knowledge of the Polish population should be filled.